Peningkatan Literasi Membaca Melalui Cerita Rakyat “Legenda Pulau Kemaro” Menggunakan Aplikasi Edpuzzle - Dinda Novita; Yeni Ernawati; Nuraini Nuraini (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This service activity was carried out as an effort by the Indonesian Language Education study program to increase students' interest in reading about the regional lore of South Sumatra. Through this reading activity, it is hoped that students will be able to discover, know and understand the moral and cultural values in the sagas of South Sumatra. The Student Creativity Program (PkM) activities are carried out in the form of counseling. PkM activities were carried out at SMK Madyatama Palembang with 38 students. After implementing this PkM, students have a good interest in reading and increase their awareness at school that reading is important